1996
DOI: 10.5636/jgg.48.1127
|View full text |Cite
|
Sign up to set email alerts
|

Raman Lidar Observations: Simultaneous Measurements of Water Vapor, Temperature and Aerosol Vertical Profiles, Part I.

Abstract: A Raman lidar was developed to observe vertical profiles of water vapor, temperature and aerosols. The lidar system can detect signal from 5 detectors simultaneously. Two vibrational Raman backscattering echoes from H2O and N2 (or 02) excited by Nd:YAG 3rd harmonics wavelength (355 nm) are used to observe the profiles of water vapor mixing ratio and atmospheric temperature (or density). Nd:YAG fundamental and 2nd harmonics wavelengths (1064 and 532 ran) are used to observe backscattering coefficient profiles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Table 1 shows the characteristics of the lidar used in this study. Details of the lidar system are given by Shibata et al [1996a], so only a brief description is given here. Three wavelengths (355, 532 and 1064 nm) of Nd:YAG laser are vertically transmitted into the atmosphere with a repetition rate of 10 Hz and the backscattered light from atmospheric gases and aerosol particles is collected with a Cassegrainian telescope.…”
Section: Raman Lidar Measurementsmentioning
confidence: 99%
“…Table 1 shows the characteristics of the lidar used in this study. Details of the lidar system are given by Shibata et al [1996a], so only a brief description is given here. Three wavelengths (355, 532 and 1064 nm) of Nd:YAG laser are vertically transmitted into the atmosphere with a repetition rate of 10 Hz and the backscattered light from atmospheric gases and aerosol particles is collected with a Cassegrainian telescope.…”
Section: Raman Lidar Measurementsmentioning
confidence: 99%
“…[For details of the Raman lidar measurement, see Shibata et al (1996), and Sakai et al (1997)]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the procedure used to analyze data are summarized in Shibata et al (1996aShibata et al ( , 1996b.…”
Section: Raman Lidar Measurement Of Water Vapor and Aerosolsmentioning
confidence: 99%
“…By using this technique, the relationship between the aerosol backscatter and/or extinction and the humidity in the troposphere has been investigated (Ansmann et al, 1992;Ferrare et al, 1997). Shibata et al (1996a) and Reichardt et al (1996) demonstrated the devices applicability for the detection of ice clouds by simultaneously measuring the humidity and the depolarization ratio profiles. Since the depolarization ratio is a measure of the nonsphericity of aerosol particles (e.g., Bohren and Huffman, 1983), it has potential for discriminating the phase of the particles (liquid droplet or solid crystal).…”
Section: Introductionmentioning
confidence: 99%